1995
DOI: 10.1080/02678299508031110
|View full text |Cite
|
Sign up to set email alerts
|

Tricritical points of smectic A to nematic phase transitions for binary liquid crystal mixtures containing cyanobiphenyls

Abstract: The tricritical point of the smectic A (SA) to nematic (N) phase transition in liquid crystals, at which the nature of the phase transition changes from first order to second order, is related to the change in the order parameter during the phase transition. In this study, I3C NMR was used to determine the order parameters of four binary liquid crystal systems as a function of temperature and composition in order to investigate the tricritical behaviour of their SA-N transition. The first system was mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the great amount of experimental data on 9CB exhibits something puzzling about the character of its SmA-to-N phase transition. Some data allow for a character either tricritical or even first order in nature. ,,, Other data exhibit a crossover second-order transition with critical exponents near its tricritical value. ,,,, Even a few years ago, some of the authors of this paper measured the specific heat of 9CB, pure and mixed with other related liquid crystals, obtaining controversial results about the SmA-to-N critical behavior. In addition to these results, Halperin, Lubensky, and Ma , published a theory, denoted as HLM theory, according to which the SmA-to-N transition should always be weakly first-order in nature.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the great amount of experimental data on 9CB exhibits something puzzling about the character of its SmA-to-N phase transition. Some data allow for a character either tricritical or even first order in nature. ,,, Other data exhibit a crossover second-order transition with critical exponents near its tricritical value. ,,,, Even a few years ago, some of the authors of this paper measured the specific heat of 9CB, pure and mixed with other related liquid crystals, obtaining controversial results about the SmA-to-N critical behavior. In addition to these results, Halperin, Lubensky, and Ma , published a theory, denoted as HLM theory, according to which the SmA-to-N transition should always be weakly first-order in nature.…”
Section: Introductionmentioning
confidence: 92%
“…Nonyloxycyanobiphenyl (9OCB) is a liquid crystal for which, to the best of our knowledge, very few studies can be found in the scientific literature. If only specific studies on phase transitions and dielectric properties of their mesophases are taken into account, the references are nearly nonexistent. , However, nonylcyanobiphenyl (9CB), the homologous compound without oxygen in the molecular formula, was and is still now subject of numerous studies, even if the subject matter is only devoted to the study of the mesophase-physical properties and the critical behavior of the phase transitions: smecticA(SmA)-to-nematic(N) and N-to-isotropic (I). The phase sequence displayed by 9OCB is exactly the same as its homologous 9CB, being on cooling from the isotropic liquid: N, SmA, and finally Cr (ordered crystalline state).…”
Section: Introductionmentioning
confidence: 99%
“…explicit toluene molecules were similarly represented by united atoms, namely aromatic -CH=, -CH 2 -and -CH 3 groups. United atom parameters were taken from the Amber united-atom force field 33 and from the work of Cross and Fung 34,35 . except for the deletion of C-H bonds as a consequence of the use of pseudoatoms, PPIC helix geometry was kept in its full detail, but bond lengths, bond angles and torsion angles were frozen at their most probable values, as collected during the MD run.…”
Section: Atomistic-level (Level 1 and 2) Description Of Poly-(n-pmentioning
confidence: 99%